If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 5) = 2(6 + x) Reorder the terms: 5(5 + x) = 2(6 + x) (5 * 5 + x * 5) = 2(6 + x) (25 + 5x) = 2(6 + x) 25 + 5x = (6 * 2 + x * 2) 25 + 5x = (12 + 2x) Solving 25 + 5x = 12 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 25 + 5x + -2x = 12 + 2x + -2x Combine like terms: 5x + -2x = 3x 25 + 3x = 12 + 2x + -2x Combine like terms: 2x + -2x = 0 25 + 3x = 12 + 0 25 + 3x = 12 Add '-25' to each side of the equation. 25 + -25 + 3x = 12 + -25 Combine like terms: 25 + -25 = 0 0 + 3x = 12 + -25 3x = 12 + -25 Combine like terms: 12 + -25 = -13 3x = -13 Divide each side by '3'. x = -4.333333333 Simplifying x = -4.333333333
| (5x^2)+10x-25=0 | | 4xy+xy+y+x+x+x+t+h+j+34=123 | | (5x^2)+4x-25=0 | | 7i/(9-2i) | | 9x-13-3x=17 | | -1(x+5)=y+3 | | (5x^2)+4x-56=0 | | 4(4+2x)=56 | | 7/1=3/4x-1 | | 4(x-2)+3(x+1)=17 | | 0.42x+0.66=0.77 | | 5a^3+30a^2=0 | | 2(5+7x)=164 | | y-3=m(x+9) | | 2y-4=5x | | 3m+7-5m+16= | | 19k-18=12 | | Log[4](2x+1)=3 | | 0,3(2-x)-2/5(31/2x-2)=1 | | 0=-16t^2+16t+25 | | F(x)=x^3-6x^2+4x-24 | | 2(6x+2)=148 | | 9/5-(-6/10) | | 5d+2+2d=51 | | 17W=12+20w | | -3/4-(-1/6) | | 8x+5y=51 | | (2/3x-4)-(1/2x+1)=1/2 | | Z=6+7i | | F(x)=x^4-2x^3-8x^2+8x+16 | | 11r+7=10r | | 48=4v-16 |